Dynamic mechanisms and spatial spillover effects of cultural tourism development in the China–Pakistan Economic Corridor - Zuhaib; Liu, Gang; Chen, Jingyao; Ali, Shuaib; Rui, Zhang; Dawood; Chen, Huan (Frontiers in Psychology, 2025)
IntroductionThis study explores the spatial spillover effects (SSE) and dynamic mechanisms of cultural tourism in the China–Pakistan Economic Corridor (CPEC). This study examines how infrastructure development, cultural integration, and spatial connectivity affect cultural tourism in Pakistan’s CPEC and non-CPEC regions using spatial spillover and Hofstede’s cultural dimensions theory.MethodsData were collected from 1,387 respondents in both regions, analyzed using the spatial Durbin model and structural equation modeling, and visualized using ArcMap and Geoda.ResultsThe results indicate that the growth of cultural tourism is strongly influenced by dynamic processes, including better infrastructure, more cultural interchange, and easier accessibility, particularly in CPEC regions. Furthermore, non-CPEC regions exhibit minor advantages in terms of indirect economic gains and increased accessibility, highlighting the ongoing inequalities.DiscussionThese findings provide empirical insights into the regional impacts of large-scale initiatives, such as CPEC, and draw attention to government intervention, equitable resource allocation, and stakeholder collaboration to achieve long-term cultural tourism.